Pengembangan Media Video Animasi Berbasis Animaker untuk Meningkatkan Hasil Belajar Materi Puisi Mapel Bahasa Indonesia Kelas 3 SD - Edwina Ariandhini; Indri Anugraheni (Peneliti.net, 2022)
Learning media according to (Surayya, 2012) is a tool that is able to assist the teaching and learning process and serves to clarify the meaning of the message or information conveyed, so as to achieve the planned learning objectives. The purpose of this study is to determine the level of validity according to expert opinion regarding the product development of Animated Video Based on ANIMAKER To Improve Learning Outcomes in Grade 3 Students. This type of research is research and development (R&D). Research using the ADDIE design model The ADDIE Development Model has stages (Analysis-Design-Development-Implementation-Evaluation). This study aims to develop Animaker-based Animation Video Learning Media to improve learning outcomes of Poetry Materials for 3rd grade elementary school students, knowing the level of product validity which includes the validity of materials, media, learning designs, and evaluation questions according to experts. The data from the validation test results are obtained as follows: (1) the percentage obtained from the material expert validation test is 97% with the assessment criteria obtained is high; (2) the percentage obtained from the media expert validation test is 78% with the assessment criteria obtained is very high. Based on the validation test from media experts and material experts, it can be concluded that the learning media in the form of Animated Video Based on ANIMAKER To Improve Learning Outcomes of Indonesian Language Lessons for Grade 3 Elementary School can be said to be feasible to use